Assessing the challenges and opportunities for small and medium enterprises (SMEs) in Thailand online retail market / Kwanrudee Prachaseree...[et al.] - Prachaseree, Kwanrudee; Ahmad, Norzieiriani; Md Isa, Normalisa (Universiti Teknologi MARA, Kedah, 2019)
Since the Thailand government focuses on its “Thailand 4.0” policy, which includes allocating a budget for the specific purpose of constructing a broadband network for all villages across the country, Small and Medium Enterprises (SMEs) have tremendously contributed to the rapid growth in the country’s economy. Although SMEs play an important role in Thailand’s online retail market, relatively little is known about Thailand’s online retailing market environment and Thai domestic online retailers’ dynamic business performance in the marketplace. Therefore, the present study aimed to extend an understanding of the competitive advantages of Thai domestic small and medium sized online retail firms and examine their growth potential in Thailand’s online retail marketplace.